Charged ultrafiltration membranes based on TEMPO-oxidized cellulose nanofibrils/poly(vinyl alcohol) antifouling coating. Issue 12 (10th February 2021) - Aguilar-Sanchez, Andrea; Jalvo, Blanca; Mautner, Andreas; Rissanen, Ville; Kontturi, Katri S.; Abdelhamid, Hani Nasser; Tammelin, Tekla; Mathew, Aji P.
Abstract : Crosslinked cellulose nanofiber-polyvinyl alcohol antifouling membrane. Abstract : This study reports the potential of TEMPO-oxidized cellulose nanofibrils (T-CNF)/poly(vinyl alcohol) (PVA) coatings to develop functionalized membranes in the ultrafiltration regime with outstanding antifouling performance and dimensional/pH stability. PVA acts as an anchoring phase interacting with the polyethersulfone (PES) substrate and stabilizing for the hygroscopic T-CNF via crosslinking. The T-CNF/PVA coated PES membranes showed a nano-textured surface, a change in the surface charge, and improved mechanical properties compared to the original PES substrate. A low reduction (4%) in permeance was observed for the coated membranes, attributable to the nanometric coating thickness, surface charge, and hydrophilic nature of the coated layer. The coated membranes exhibited charge specific adsorption driven by electrostatic interaction combined with rejection due to size exclusion (MWCO 530 kDa that correspond to a size of ∼35–40 nm). Furthermore, a significant reduction in organic fouling and biofouling was found for T-CNF/PVA coated membranes when exposed to BSA and E. coli . The results demonstrate the potential of simple modifications using nanocellulose to manipulate the pore structure and surface chemistry of commercially available membranes without compromising on permeability and mechanical stability.